The Adsorption of Methylene Blue by an Amphiphilic Block Co-Poly(Arylene Ether Nitrile) Microsphere-Based Adsorbent: Kinetic, Isotherm, Thermodynamic and Mechanistic Studies - Xuefei Zhou; Mingzhen Xu; Lingling Wang; Xiaobo Liu (Nanomaterials, 2019)
Dye pollution is a serious problem in modern society. We desired to develop an efficient adsorbent for the decontamination of discharged dyes. In this work, the polymeric microspheres derived from a kind of amphiphilic block of co-poly(arylene ether nitrile) (B-b-S-P) were prepared on the basis of “oil-in-water” (O/W) microemulsion method. The B-b-S-P microspheres were found competent to remove the cationic dye, methylene blue (MB); and various influential factors, such as contact time, initial concentration, solution pH and temperature were investigated. Results indicated that the maximum adsorption capacity of B-b-S-P microspheres for MB was 119.84 mg/g at 25 °C in neutral conditions. Adsorption kinetics and isotherm dates were well fitted to a pseudo-second-order kinetic model and the Langmuir isotherm model, and thermodynamic parameters implied that the adsorption process was endothermic. The B-b-S-P microspheres also exhibited a highly selective adsorption for cationic dye MB, even in the presence of anionic dye methyl orange (MO). In addition, the possible adsorption mechanism was studied, suggesting that the electrostatic interaction and π−π interaction could be the main force in the adsorption process.